Culture and the Labor Supply of Female Immigrants - Julia Bredtmann; Sebastian Otten (Institute of Labor Economics (IZA), 2022)
This paper analyzes the impact of source-country culture on the labor supply of female immigrants in Europe. We find that the labor supply of immigrant women is positively associated with the female-to-male labor force participation ratio in their source country, which serves as a proxy for the country's preferences and beliefs regarding women's roles. This suggests that the culture and norms of their source country play an important role for immigrant women's labor supply. However, contradicting previous evidence for the U.S., we do not find evidence that the cultural effect persists through the second generation.
Keywords: J16; J22; J61; 330; female labor force participation; immigration; integration; cultural transmission; epidemiological approach